2004
DOI: 10.1111/j.1349-7006.2004.tb03251.x
|View full text |Cite
|
Sign up to set email alerts
|

c‐kit gene mutations in intracranial germinomas

Abstract: Gain-of-function mutations of the c-kit gene and the expression of phosphorylated KIT are found in most gastrointestinal stromal tumors and mastocytosis. Further, almost all gonadal seminomas/ dysgerminomas exhibit KIT membranous staining, and several reports have clarified that some (10-25%) have a c-kit gene mutation. But, whether intracranial germinomas also have a c-kit gene mutation remains unsolved. To elucidate the presence, frequency, and location of c-kit gene mutations in intracranial germinomas, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 31 publications
2
57
3
Order By: Relevance
“…[10][11][12][13][14][15] To investigate this discrepancy and to further characterize the types of c-kit mutations in semi- c-kit mutations in seminoma C Willmore-Payne et al nomas, we used a new methodology referred to as high-resolution melting amplicon analysis, to screen 22 pure testicular seminomas for c-kit-activating mutations. After PCR amplification of genomic DNA from a tumor with a c-kit-activating mutation, a mixture of DNA molecules is obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] To investigate this discrepancy and to further characterize the types of c-kit mutations in semi- c-kit mutations in seminoma C Willmore-Payne et al nomas, we used a new methodology referred to as high-resolution melting amplicon analysis, to screen 22 pure testicular seminomas for c-kit-activating mutations. After PCR amplification of genomic DNA from a tumor with a c-kit-activating mutation, a mixture of DNA molecules is obtained.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Most reports describe point mutations in exon 17, but occasional exon 11 mutations have also been noted. [12][13][14][15] The frequency of these mutations in seminomas has been reported to range up to 41%. 14 The majority of the exon 17 mutations reported (D816V) code for a c-kit protein that is probably imatinib resistant.…”
mentioning
confidence: 99%
“…Therefore, it is conceivable that auto-activating mutations of the cKIT gene (exon 17: D816V, D816H, N822K, Y823D; exon 11: L576P, W557C), rendering cKIT expression independent of SCF, might cause erroneous migration of PGCs, eventually leading to formation of intracranial germinomas (Przygodzki et al 2002, Kemmer et al 2004, WillmorePayne et al 2006, Biermann et al 2007). Sakuma and coworkers and Kamakura and coworkers demonstrated cKIT expression in all germinomas or germinomatous components of mixed non-germinomas (Sakuma et al 2004, Kamakura et al 2006. Additionally, Sakuma and coworkers found that 25% of all germinomas analyzed harbored an autoactivating cKIT mutation at exon 11 or 17, while Kamakura and co-workers detected mutated cKIT in 23% of germinomas (exon 2 (E73K, T96M), 11 (V560D), 13 (A636V), 17 (D816Y)) (Sakuma et al 2004, Kamakura et al 2006).…”
Section: Germinoma: Misrouting Of Germ Cells By Defects In Ckit or Cxcr4mentioning
confidence: 99%
“…Sakuma and coworkers and Kamakura and coworkers demonstrated cKIT expression in all germinomas or germinomatous components of mixed non-germinomas (Sakuma et al 2004, Kamakura et al 2006. Additionally, Sakuma and coworkers found that 25% of all germinomas analyzed harbored an autoactivating cKIT mutation at exon 11 or 17, while Kamakura and co-workers detected mutated cKIT in 23% of germinomas (exon 2 (E73K, T96M), 11 (V560D), 13 (A636V), 17 (D816Y)) (Sakuma et al 2004, Kamakura et al 2006). These mutation rates are very similar to the cKIT mutation rates found in classical seminoma (24.1%) (Sakuma et al 2003, Kemmer et al 2004.…”
Section: Germinoma: Misrouting Of Germ Cells By Defects In Ckit or Cxcr4mentioning
confidence: 99%
“…The importance of these findings is that molecular targeting agents, such as imatinib, which is an inhibitor of specific tyrosine kinases, including KIT, can be used in the management of GGCTs that harbor KIT mutations. These alternative management options can help avoid long-term adverse effects associated with radiotherapy which include neurocognitive impairment, secondary neoplasms, radiation-induced occlusive vasculopathy, and endocrinological dysfunctions [29,30]. The relationship between KIT mutations and the prognosis of GGCTs is controversial [31].…”
Section: Molecular Oncology Of Gctsmentioning
confidence: 99%